Pembuatan Selai Kopi sebagai Inovasi Produk di Desa Tapak Gedung Kabupaten Kepahiang Bengkulu - Fadhilah, Nurul; Achmad, Feerzet; Sylvia, Teny; Hatta, Madani (Jurnal Ilmiah Pangabdhi, 2024)
Coffee is one of the leading commodities in Indonesia. Indonesia is one of the largest coffee producers in the world. Jam is a type of semi-wet food through a cooking process made by adding a combination of fruits, sugar, without food additives or food additives that have been permitted. Coffee jam is one form of product diversification made from original ground coffee. In this jam making activity add granulated sugar as another main component. Tapak Gedung Village, which is one of the villages in Tebat Karai District, Kepahiang Regency, Bengkulu Province, has natural resources and coffee potential that supports. Coffee is the crop of the majority of the local population. Arabica and Robusta coffee types are the most widely cultivated. The level of coffee liking among the people is very high, and it has become a daily routine to consume it. Therefore, it is necessary to make coffee product innovations that aim to create a different sensation when consuming coffee, extend shelf life, and are expected to increase selling value that is beneficial to the local community. Furthermore, to support the success of making coffee jam, organoleptic test questionnaire sheets related to taste, aroma, color and texture were distributed to village and community officials.